The body in the trees : a novel - Fletcher, Jessica; Moran, Terrie Farley (Fletcher, Jessica. Murder, she wrote, 2025)
"It's leaf-peeping season in Cabot Cove, but for someone, it's killing season! A quartet of friends from Florida have come to Maine to experience a colorful New England autumn, complete with hiking in the woods and fishing for haddock and crabs. When one of the tourists goes missing, the town rallies to find Wendy Lu Shaffer, who must simply be lost in the woods. After all, crime is rare in Cabot Cove, if you discount the so-called Bicycle Bandit who's been riding around town snatching women's purses. Then Jessica Fletcher and Dan Andrews, editor of the Cabot Cove Gazette, bump into each other while biking along the ridge outside town. Dan looks down and sees a leg caught in the branches of a tree. Wendy Lu has been found, and her three friends seem devastated. No one knows what she was doing alone on the ridge, or how she came to fall. Concerned about losing tourist dollars, the mayor wants the death ruled an accident, but Jessica believes it was murder. She won't rest until she knows whether Wendy Lu came to Cabot Cove for more than sightseeing-and what led to her death amid the trees"--